A systematic review and meta‐analysis of intervention characteristics in postpartum weight management using the TIDieR framework: A summary of evidence to inform implementation. (3rd April 2019) - Lim, Siew; Liang, Xinyu; Hill, Briony; Teede, Helena; Moran, Lisa J.; O'Reilly, Sharleen
Summary: Postpartum weight retention is a significant contributor to obesity in reproductive‐aged women, but the key implementation characteristics of postpartum weight management interventions have not been systematically identified to inform policy and practice. This study aimed to evaluate the intervention characteristics associated with weight loss in postpartum women using the Template for Intervention Description and Replication (TIDieR) framework. We searched MEDLINE, CINAHL, EMBASE, PSYCINFO, and EBM databases to identify lifestyle intervention RCTs in postpartum women (within 2 years after birth) published up to January 2018. From 4512 studies, 33 studies were included in the systematic review and meta‐analysis (n = 4960 women). Health professional‐delivered interventions had significantly greater weight loss than those delivered by nonhealth professionals (mean difference, 95% confidence interval: (−3.22 kg [−4.83, −1.61] vs −0.99 kg [−1.53, −0.45], P  = 0.01 for subgroup differences)). Diet and physical activity combined had significantly greater weight loss compared with physical activity‐only interventions (−3.15 kg [−4.34, −1.96] vs −0.78 kg [−1.73, 0.16], P  = 0.009 for subgroup differences). The extent of weight loss was not influenced by intervention intensity (duration, number of sessions) and setting (individual or group).